2003
DOI: 10.1902/jop.2003.74.12.1808
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Healing Following Space Creation in rhBMP‐2–Induced Periodontal Regeneration of Horizontal Circumferential Defects in Dogs with Experimental Periodontitis

Abstract: Implantation of rhBMP-2/PGS enhances bone formation and connective tissue attachment in horizontal circumferential defects. In addition, the use of a spacer membrane reduces the degree of bone formation, but minimizes ankylosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 24 publications
2
40
0
Order By: Relevance
“…The most studied BMPs for bone regeneration applications are BMP-2 and BMP-7 [336,337]. Many preclinical studies have shown the usefulness of recombinant human BMPs for the regeneration of bone tissue [338,339,340,341]. Bone defect healing using genetic approach where an implant comprising of a bioresorbable polymer mixed with mesenchymal stem cells transfected with adenovirus BMP-2 has been demonstrated [342].…”
Section: Developments and The Future Of Bone Augmentationmentioning
confidence: 99%
“…The most studied BMPs for bone regeneration applications are BMP-2 and BMP-7 [336,337]. Many preclinical studies have shown the usefulness of recombinant human BMPs for the regeneration of bone tissue [338,339,340,341]. Bone defect healing using genetic approach where an implant comprising of a bioresorbable polymer mixed with mesenchymal stem cells transfected with adenovirus BMP-2 has been demonstrated [342].…”
Section: Developments and The Future Of Bone Augmentationmentioning
confidence: 99%
“…On the upper jaw, intraosseous defects on premolars and molars were also described [45, 58, 59]. The number of residual osseous walls present at the level of the surgical defect was considered to be an important factor for healing.…”
Section: The Different Animal Models In Periodontologymentioning
confidence: 99%
“…Among several growth factors, platelet-derived growth factor (PDGF) (20, 21), fibroblast growth factor-2 (FGF-2) (22, 23), amelogenin (24, 25), and bone morphogenetic proteins (BMPs) (7, 13, 26) are well known to have peri-odontal regeneration potential ( see Table 18.1). …”
Section: Methodsmentioning
confidence: 99%